Preparation method and application of flexible self-supporting cobalt-nitrogen-carbon composite catalyst

By growing carbon nanotube-encapsulated cobalt nanoparticles in situ on the carbon cloth, a flexible self-supported cobalt-nitrogen-carbon composite catalyst was prepared, which solved the problem of expensive and poor stability of precious metal-based catalysts, and achieved efficient catalysis and stability improvement of ORR/OER reaction in zinc-bath batteries.

CN119695179AActive Publication Date: 2025-03-25XINJIANG UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411881323.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The precious metal-based catalysts used in existing zinc-air batteries have problems such as expensive and poor electrochemical stability. The traditional powdered non-precious metal catalysts are prone to fall off during charging and discharging, which reduces the stability of the catalyst.

Method used

A flexible self-supported cobalt-nitrogen-carbon composite catalyst is used to form a Co/NCNTs/CC catalyst by growing carbon nanotubes in situ on a carbon cloth, which has good flexibility and stability.

Benefits of technology

This catalyst exhibits excellent ORR/OER dual-function electrocatalytic performance in an alkaline environment, improving the stability and application prospects of zinc-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695179A_ABST
    Figure CN119695179A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of zinc-air battery catalysts, and discloses a preparation method and application of a flexible self-supporting cobalt-nitrogen-carbon composite catalyst. The metal formic acid framework grows on the carbon cloth in situ, the Co / NCNTs / CC catalyst is obtained through one-step pyrolysis, the Co / NCNTs / CC serves as an ORR / OER electrocatalyst, the Co / NCNTs / CC has better catalytic performance compared with Pt / C and RuO2 noble metal catalysts, and reference is provided for improving the performance of non-noble metal catalysts. A liquid zinc-air battery and a flexible zinc-air battery which are assembled by taking Co / NCNTs / CC as the air cathode show good electrochemical performance and stability and have a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc-air battery catalysts, and more specifically relates to a preparation method and application of a flexible self-supporting cobalt-nitrogen-carbon composite catalyst. Background Art

[0002] Due to the serious energy dilemma and the increasingly serious ecological crisis worldwide, sustainable and environmentally friendly energy conversion technologies have attracted much attention. Zinc-air battery (ZAB), as a new type of electrochemical energy storage device, is favored by people because of its relatively safe and stable use, cheap and easy-to-obtain raw materials, and the battery can be recycled. However, during the charging and discharging process of ZAB, the oxygen reaction in the air cathode, namely the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR), has a slow chemical kinetic process, which makes the actual potential of the reaction much higher than the theoretical potential; currently, noble metal-based catalysts such as Pt / C and RuO2 are commonly used in ZAB cathodes to accelerate the oxygen reaction kinetics and reduce the reaction potential; however, noble metal-based catalysts have problems such as high price and poor electrochemical stability. Therefore, the research on the development of non-noble metal catalysts with high catalytic activity as air cathode materials has attracted much attention.

[0003] To date, there are a variety of catalysts for ORR / OER, including metal-nitrogen-carbon, transition metal compounds, and carbon materials without metal heteroatom doping. All of them enhance the reaction rate of electrocatalysts by adjusting the surface structure and electronic structure of the material. Among them, metal-nitrogen-carbon materials have good activity characteristics due to their easy access, low economic cost, and synergistic co-doping effect between metal and nitrogen, and are considered to be the most promising alternatives to bifunctional precious metal catalysts. Metal-organic frameworks have attracted widespread attention due to their own advantages such as adjustable morphology and structure, rich pores, and active chemical properties. However, their stability is poor and they are usually in powder form. When assembling zinc-air batteries, a binder is required to attach them to the electrode surface. As the reaction time is too long, the catalyst is easy to fall off, which greatly reduces the stability of the catalyst.

[0004] Therefore, how to provide a simple and easy method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst to further reduce the overpotential in the ORR / OER reaction and improve the catalyst stability has very important research significance and application value. Summary of the invention

[0005] In view of the shortcomings of traditional powdered ORR / OER bifunctional catalysts, the present invention provides a method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst and its application in a flexible zinc-air battery. The carbon nanotube-encapsulated cobalt nanoparticle catalyst grown in situ on the carbon cloth obtained by the present invention is evenly distributed and has good flexibility. It exhibits good ORR / OER bifunctional electrocatalytic performance in an alkaline environment. At the same time, the assembled liquid zinc-air battery and flexible zinc-air battery have good stability and good application prospects.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst comprises the following steps:

[0008] (1) ultrasonically cleaning the carbon cloth in acetone, sulfuric acid, and water in sequence, removing the surface coating, and vacuum drying;

[0009] (2) dissolving cobalt nitrate hexahydrate, urea, and ammonium fluoride in deionized water, and then adding the treated carbon cloth into a reactor for hydrothermal reaction, and drying to obtain cobalt hydroxide Co(OH)2 / CC grown in situ on the carbon cloth;

[0010] (3) dissolving methylamine, formic acid and AEO-3 in n-octane to obtain a ligand solution; dissolving cobalt nitrate hexahydrate, zinc nitrate hexahydrate, methanol and AEO-3 in n-octane to obtain a metal salt solution; quickly pouring the metal salt solution into the ligand solution to obtain a mixed solution, then immersing Co(OH)2 / CC in the mixed solution, slowly stirring with a magnetic force, then taking out the product, washing it, and drying it to obtain a zinc cobalt formate framework in situ grown on Co(OH)2 / CC, namely, ZnCo-FF / Co(OH)2 / CC;

[0011] (4) ZnCo-FF / Co(OH)2 / CC and dicyandiamide were placed at both ends of a quartz boat and placed in a tubular furnace for two-stage temperature-raising calcination to obtain a composite catalyst Co / NCNTs / CC.

[0012] Preferably, the molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step (2) is 1.5:10:5.

[0013] Preferably, the hydrothermal reaction time in step (2) is 4 hours and the temperature is 120°C.

[0014] Preferably, in step (3), the molar ratio of formic acid, methylamine, cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 6:4:0.025:0.975;

[0015] The volume ratio of n-octane to AEO-3 in the ligand solution is 25:8;

[0016] The volume ratio of n-octane, AEO-3 and methanol in the metal salt solution is 25:8:5.

[0017] Preferably, the magnetic stirring time in step (3) is 20 minutes.

[0018] Preferably, the heating rate in step (4) is 5°C / min.

[0019] Preferably, the calcination temperature of the first stage in step (4) is 400°C.

[0020] Preferably, the second calcination temperature in step (4) is 700-900°C.

[0021] The beneficial effects of the above technical solution are as follows: the second stage of heating is a carbonization process. During high-temperature carbonization, the metal will catalyze the growth of carbon nanotubes. The temperature will affect the growth rate and morphology of the carbon nanotubes, thereby affecting their catalytic performance.

[0022] Preferably, the mass ratio of dicyandiamide to ZnCo-FF / Co(OH)2 / CC in step (4) is 6:1.

[0023] The present invention also provides application of the composite catalyst prepared by the preparation method in a flexible zinc-air battery.

[0024] It can be seen from the above technical solution that, compared with the prior art, the present invention provides a method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst and its application, which has the following beneficial effects:

[0025] The present invention designs a simple and feasible preparation method, in which the metal formate framework is grown in situ on carbon cloth, and the Co / NCNTs / CC catalyst is obtained by one-step pyrolysis. Co / NCNTs / CC as an ORR / OER electrocatalyst has better catalytic performance than Pt / C and RuO2 noble metal catalysts, providing a reference for improving the performance of non-noble metal catalysts. Liquid zinc-air batteries and flexible zinc-air batteries assembled with Co / NCNTs / CC as air cathodes show good electrochemical performance and stability, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1a and b are scanning electron microscope images of Co(OH)2 / CC obtained in Example 1.

[0028] Figure 2 a and b are scanning electron microscope images of ZnCo-FF / Co(OH)2 / CC obtained in Example 1.

[0029] Figure 3 a and b are scanning electron microscope images of Co / NCNTs / CC-1 obtained in Example 1.

[0030] Figure 4 a is the X-ray powder diffraction pattern of Co(OH)2 / CC and ZnCo-FF / Co(OH)2 / CC obtained in Example 1, Figure 4 b is the X-ray powder diffraction pattern of the products obtained in each embodiment and comparative example.

[0031] Figure 5 In the figure, a and b are the ORR linear sweep voltammetry curves and the corresponding Tafel slopes of the products obtained in each embodiment and comparative example, respectively.

[0032] Figure 6 In the figure, a and b are the OER linear sweep voltammetry curves and the corresponding Tafel slopes of the products obtained in each embodiment and comparative example, respectively.

[0033] Figure 7 In the figure, a and b are the cycle charge and discharge curves of the liquid zinc-air battery and the flexible zinc-air battery assembled by Co / NCNTs / CC-1 obtained in Example 1, respectively. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst comprises the following steps:

[0037] (1) The carbon cloth was cut into pieces of 1 cm × 2 cm, and ultrasonically cleaned with acetone and 0.5 M sulfuric acid, and then ultrasonically cleaned with distilled water, and the surface coating was removed and then taken out and vacuum dried;

[0038] (2) Cobalt nitrate hexahydrate (1.5 mmol), urea (10 mmol), and ammonium fluoride (5 mmol) were dissolved in 35 mL of deionized water, and then added together with the treated carbon cloth into a 50 mL reactor, and subjected to hydrothermal reaction at 120 ° C for 4 h, and then dried in a vacuum oven at 60 ° C for 12 h to obtain cobalt hydroxide in situ grown on the carbon cloth, namely Co(OH)2 / CC, as shown in FIG. Figure 1 As shown in a and b;

[0039] (3) Methylamine (4 mmol), formic acid (6 mmol) and AEO-3 (8 mL) were dissolved in 25 mL of n-octane to obtain a ligand solution; cobalt nitrate hexahydrate (0.025 mmol), zinc nitrate hexahydrate (0.975 mmol), methanol (5 mL) and AEO-3 (8 mL) were then dissolved in 25 mL of n-octane to obtain a metal salt solution; the metal salt solution was quickly poured into the ligand solution to obtain a mixed solution, and Co(OH)2 / CC was immersed in the mixed solution, slowly magnetically stirred for 20 min, and then the product was taken out, then rinsed with anhydrous ethanol, and dried in a vacuum oven at 60°C for 12 h to obtain a zinc cobalt formate framework in situ grown on Co(OH)2 / CC, namely, ZnCo-FF / Co(OH)2 / CC, as shown in FIG. Figure 2 As shown in a and b;

[0040] (4) Dicyandiamide (0.3 g) and ZnCo-FF / Co(OH)2 / CC (0.05 g) were placed in two sections of a quartz boat, which was placed in a tube furnace. The side containing dicyandiamide was placed upstream of the gas flow. Under a N2 atmosphere, the temperature was increased at a rate of 5°C / min. The first section was heated to 400°C and kept at this temperature for 2 h, and the second section was heated to 800°C and kept at this temperature for 2 h. The mixture was naturally cooled to room temperature to obtain a self-supporting electrocatalyst of nitrogen-carbon nanotubes encapsulated cobalt nanoparticles grown in situ on carbon cloth, namely, a composite catalyst Co / NCNTs / CC-1, as shown in FIG. Figure 3 As shown in a and b.

[0041] Example 2

[0042] The difference from Example 1 is that in step (4), the second stage is heated to 700° C. and kept warm for 2 h, and the rest is the same. A self-supporting electrocatalyst of nitrogen-carbon nanotubes encapsulating cobalt nanoparticles grown in situ on carbon cloth is obtained, namely, a composite catalyst Co / NCNTs / CC-2.

[0043] Example 3

[0044] The difference from Example 1 is that in step (4), the second stage is heated to 900°C and kept warm for 2 hours, and the rest is the same. A self-supporting electrocatalyst of nitrogen-carbon nanotubes encapsulating cobalt nanoparticles grown in situ on carbon cloth is obtained, namely, a composite catalyst Co / NCNTs / CC-3.

[0045] Comparative Example 1

[0046] The difference from Example 1 is that after step (2) is completed, step (4) is directly carried out, 0.3 g of dicyandiamide and Co(OH)2 / CC are treated at high temperature, and naturally cooled to room temperature to obtain Co / NC / CC.

[0047] Comparative Example 2

[0048] Commercial catalysts Pt / C (20 wt%) and RuO2 were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0049] The scanning electron microscopy images of Co(OH)2 / CC and ZnCo-FF / Co(OH)2 / CC obtained in Example 1 are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that ZnCo-FF grows uniformly on Co(OH)2 / CC through room temperature precipitation method.

[0050] The scanning electron microscope image of Co / NCNTs / CC-1 obtained in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that the carbonized sample becomes carbon nanotubes evenly distributed on the carbon cloth. Such a structure is more conducive to exposing active sites and improving the catalytic performance of the material.

[0051] Depend on Figure 4 a It can be seen that Co(OH)2 / CC and ZnCo-FF / Co(OH)2 / CC have been successfully prepared, which is consistent with the results of SEM test. Figure 4 b It can be seen that in addition to two obvious broad diffraction peaks for carbon cloth, there are also some small diffraction peaks for cobalt metal.

[0052] The ORR electrocatalytic performance of the products obtained in each embodiment and comparative example is as follows: Figure 5 As shown. Figure 5 a It can be seen that in 0.1 M KOH, the half-wave potential of Co / NCNTs / CC-1 is 0.87 V, showing better catalytic performance than Pt / C.

[0053] The OER electrocatalytic performance of the products obtained in each embodiment and comparative example is as follows: Figure 6 As shown. Figure 6 a It can be seen that in 1MKOH, Co / NCNTs / CC-1 has a -2 At a current density of , the oxygen evolution reaction only requires an overpotential of 243 mV, showing catalytic performance superior to that of RuO2.

[0054] The charge and discharge test curves of the liquid zinc-air battery and the flexible zinc-air battery assembled by Co / NCNTs / CC-1 obtained in Example 1 are as follows: Figure 7 As shown. The liquid zinc-air battery uses Co / NCNTs / CC-1 as the air cathode, 6mol / L KOH+0.2mol / L zinc acetate aqueous solution as the electrolyte, and zinc sheet as the anode. Figure 7 a It can be seen that: at 10mA·cm -2 At a current density of , the liquid zinc-air battery assembled by Co / NCNTs / CC-1 showed 500 cycles of cycling stability. The flexible zinc-air battery uses Co / NCNTs / CC-1 as the air cathode, polyvinyl alcohol as the gel electrolyte, and zinc sheet as the anode. Figure 7 b It can be seen that at 1 mA·cm -2 At a current density of 1.3 Å, the flexible zinc-air battery assembled with Co / NCNTs / CC-1 exhibited a 6-hour bending charge-discharge capability. This indicates that Co / NCNTs / CC-1 has excellent ORR / OER catalytic performance and has good application prospects.

[0055] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst, characterized in that: The following steps are involved: (1) ultrasonically cleaning the carbon cloth in acetone, sulfuric acid, and water in sequence, removing the surface coating, and vacuum drying; (2) dissolving cobalt nitrate hexahydrate, urea, and ammonium fluoride in deionized water, and then adding the treated carbon cloth into a reactor for hydrothermal reaction, and drying to obtain cobalt hydroxide Co(OH)2 / CC grown in situ on the carbon cloth; (3) dissolving methylamine, formic acid and AEO-3 in n-octane respectively to obtain a ligand solution; dissolving cobalt nitrate hexahydrate, zinc nitrate hexahydrate, methanol and AEO-3 in n-octane to obtain a metal salt solution; quickly pouring the metal salt solution into the ligand solution to obtain a mixed solution, then immersing Co(OH)2 / CC in the mixed solution, slowly stirring with a magnetic force, then taking out the product, washing and drying it to obtain a zinc cobalt formate framework in situ grown on Co(OH)2 / CC, i.e., ZnCo-FF / Co(OH)2 / CC; (4) ZnCo-FF / Co(OH)2 / CC and dicyandiamide were placed at both ends of a quartz boat and placed in a tubular furnace for two-stage temperature-raising calcination to obtain a composite catalyst Co / NCNTs / CC.

2. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step (2) is 1.5:10:

5.

3. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The hydrothermal reaction time in step (2) is 4 hours and the temperature is 120°C.

4. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: In step (3), the molar ratio of formic acid, methylamine, cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 6:4:0.025:0.975; The volume ratio of n-octane to AEO-3 in the ligand solution is 25:8; The volume ratio of n-octane, AEO-3 and methanol in the metal salt solution is 25:8:

5.

5. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The magnetic stirring time in step (3) is 20 minutes.

6. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The heating rate in step (4) is 5°C / min.

7. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The calcination temperature of the first stage in step (4) is 400°C.

8. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The calcination temperature of the second stage in step (4) is 700-900°C.

9. The method for preparing a flexible self-supporting cobalt-nitrogen-carbon composite catalyst according to claim 1, characterized in that: The mass ratio of dicyandiamide to ZnCo-FF / Co(OH)2 / CC in step (4) is 6:

1.

10. Use of the composite catalyst prepared according to the preparation method of claims 1 to 9 in liquid zinc-air batteries and flexible zinc-air batteries.

Citation Information

Patent Citations

  • Method for preparing three-dimensional graded-pore nitrogen-phosphorus-doped carbon confinement CoxP nanocrystalline composite material, composite material and application of three-dimensional graded-pore nitrogen-phosphorus-doped carbon confinement CoxP nanocrystalline composite material

    CN117543031A

  • Preparation method of H-CoFe-CNT micro-nano composite material and zinc air battery

    CN118993038A

  • Catalyst for rechargeable energy storage devices and method for making the same

    US20220037675A1